Physical Activity in Mexican High Schools. (26th May 2022) - Díaz‐Muñoz, Irving; Lozada‐Tequeanes, Ana L.; Campos‐Nonato, Ismael; Franco‐Lares, Bianca S.; Bonvecchio, Anabelle
Abstract: Background: We evaluated the association between availability of specific physical activity (PA) spaces and PA practices among adolescents within Mexican high schools (HS). Methods: Data were collected through an online survey applied to principals or person in charge of 4023 Mexican HS during the 2015‐2016 school year. Adequate PA was defined as moderate to vigorous intensity PA for ≥60 minutes/day, ≥5 days/week, whereas PA‐specific spaces were considered those that were available and specifically designed/used for PA. HS demographic factors were explored as covariates. Associations were estimated using a logistic regression model. Results: From total participating HS, 83.10% had at least 1 PA‐specific space and 31.07% had adequate PA practices. A higher number of PA‐specific spaces was associated with greater adequate PA practices (33% to 61%). Possibilities for adequate PA increased when: physical education (PE) classes were led by a designated PE teacher (OR 2.39; 95%CI: 2.03‐2.83); the number of enrolled students was higher (OR 1.78; 95%CI, 1.43‐2.22 and OR 2.23; 95% CI, 1.71‐2.89, second and third tertile, respectively); HS financing sources were autonomous or private (OR 1.76; 95% CI, 1.19‐2.60); and HS were located in northern Mexico (OR 1.27; 95%CI, 1.02‐1.57). Conclusion: PA‐specific spaces, designated PE teachers, and financing sources are important factors in achieving adequate PA within Mexican high schools.